A higiene como missão: Fundação Rockefeller, filantropia e controvérsia científica Paraíba do Norte (1923 1930) - Paloma Porto Silva (2014)
This thesis aims to study the process by which the North-American scientific philanthropy was inserted in the Brazilian state of Paraíba do Norte between 1923 and 1930, from the agreement reached between Paraíbas government and the Rockefeller Foundation. To achieve such an objective, we analyzed the scientific practices spread by the actors involved in the actions to fight the Yellow Fever to evidence that the Key focus epidemiological theory was the scientific basis utilized by the Rockefellers physicians and was the point of controversy with the local physicians. We apprehended that the North-American attempts to eradicate Yellow Fever constituted of an problematic enterprise that involved the accommodation of political, scientific and professional interests. In despite of Paraibas doctors, specially Dr. Walfredo Guedes Pereira, warnings to the idea of endemicity of the disease in Paraíbas little cities and towns of the countryside what would cost a lot more money to fight , the physicians of Rockefeller Foundation, chiefly Dr. Michael Edward Connor, insisted in keeping the antivectorial services in the coast and in the bigger cities, based on their epidemiological theory. Therefore, this thesis tried to investigate the trajectory of the North-Americans Dr. Michael Connor and Dr. John Austin Kerr who, like many other foreigners, searched for scientific success and acknowledgment in their Public Health enterprises. In Paraiba, this doctors found themselves in the middle of deep struggles with Dr. Walfredo Guedes Pereira. Exciting religious interpretations are revealed in this scientific quarrel: the North-Americans held, among other convictions, their predestination as redeemers of the uncivilized. However, we dont close our research with this observation to give emphasis on the letters exchanged, in the private sphere, by the doctors involved. Thus, by the aegis of philanthropists, were hidden doctors eager for acknowledgment.